Elastin-Like Protein, with Statherin Derived Peptide, Controls Fluorapatite Formation and Morphology - Shuturminska, Kseniya; Tarakina, Nadezda V.; Azevedo, Helena S.; Bushby, Andrew J.; Mata, Alvaro; Anderson, Paul; Al-Jawad, Maisoon (Frontiers in Physiology, 2017)
The process of enamel biomineralization is multi-step, complex and mediated by organic molecules. The lack of cells in mature enamel leaves it unable to regenerate and hence novel ways of growing enamel-like structures are currently being investigated. Recently, elastin-like protein (ELP) with the analog N-terminal sequence of statherin (STNA15-ELP) has been used to regenerate mineralized tissue. Here, the STNA15-ELP has been mineralized in constrained and unconstrained conditions in a fluoridated solution. We demonstrate that the control of STNA15-ELP delivery to the mineralizing solution can form layered ordered fluorapatite mineral, via a brushite precursor. We propose that the use of a constrained STNA15-ELP system can lead to the development of novel, bioinspired enamel therapeutics.